2001
DOI: 10.1002/1521-3765(20010817)7:16<3526::aid-chem3526>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Formation of BaSO4 Fibres with Morphological Complexity in Aqueous Polymer Solutions

Abstract: BaSO4 fibres with morphological complexity were formed in aqueous solution with polyacrylate and partially monophosphonated poly(ethyleneoxide)-block-poly(methacrylic acid) additives by a simple precipitation reaction. For polyacrylate, formation of the fibrous deposits was strongly dependent on the level of supersaturation (S) and Ba2+:polymer molar ratio (R). At S = 60 to 80, and R = 3 to 14, highly anisotropic crystalline fibres consisting of bundles of BaSO4 nanofilaments were formed after several weeks, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
154
1
8

Year Published

2002
2002
2014
2014

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 173 publications
(182 citation statements)
references
References 28 publications
19
154
1
8
Order By: Relevance
“…The crystallization involves the formation of different hierarchical structures like rods through dumbbell to flower shaped which have never been seen before in natural biominerals. Proteins and polysaccharides with complicated patterns of various functional groups in GA selectively adsorb on to the metal ion thereby hindering the crystal growth, followed by the mesoscale self-assembly of nanometer-scale building block into hierarchial superstructures [38][39][40][41][42]. The key reaction of CO 2 with Ba 2+ ions entrapped within GA polymer leads to the growth of beautiful structures of witherite nanocrystalline, such an aggregated morphology not normally observed using other surfaces as templates.…”
Section: Introductionmentioning
confidence: 99%
“…The crystallization involves the formation of different hierarchical structures like rods through dumbbell to flower shaped which have never been seen before in natural biominerals. Proteins and polysaccharides with complicated patterns of various functional groups in GA selectively adsorb on to the metal ion thereby hindering the crystal growth, followed by the mesoscale self-assembly of nanometer-scale building block into hierarchial superstructures [38][39][40][41][42]. The key reaction of CO 2 with Ba 2+ ions entrapped within GA polymer leads to the growth of beautiful structures of witherite nanocrystalline, such an aggregated morphology not normally observed using other surfaces as templates.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, in a strongly related field, bio-inspired morphosynthesis using designed artificial organic templates offers another approach in generating inorganic crystals with unusual structure specialty and complexity [5]. For example, in the case of BaSO 4 , a variety of morphologies including cones, multiple-cones [6], peanuts and flowers with a crystallographically forbidden ten-fold symmetry [7] as well as complex bundles and superstructures [8] have been obtained by utilizing various double hydrophilic block copolymers as crystal modifiers.…”
mentioning
confidence: 99%
“…[16][17][18][19] Particularly in the calcium phosphate system, Antonietti et al reported back in 1998 the stabilization of delicate neuron-like calcium phosphate structures with the help of a DHBC consisting of a long poly(ethylene oxide) block and a short poly(methacrylic acid) block partially alkylated with dodecylamine (PEO-block-PMMA-C12). 20 These structures were again replicated by Tjandra et al in 2005 using a similar design of the DHBC (PEO-block-PMMA) but with a longer PMMA chain.…”
Section: 10mentioning
confidence: 94%